Faktor-faktor Pendukung dan Penghambat Pelaksanaan Kegiatan Ekstrakurikuler dalam Pembinaan Karakter Disiplin Siswa - Yogi Nugraha; Lusiana Rahmatiani (Jurnal Moral Kemasyarakatan, 2018)
This study aimed to describe the Factors Supporting and Inhibiting Implementation of Extracurricular Activities in Student Discipline Character Development learner Se SMP in Karawang. This study used a qualitative approach with case study method. SMP entire study population Se-Karawang, sampling using purposive sampling Junior High School 1 Karawang Barat, Junior High School 1 Karawang Timur, Junior High School 1 Cilamaya Wetan, Junior High School 1 and Junior High School 1 Jatisari Banyusari. Research results supporting factors such as extracurricular activities of students is so great vigor while inhibiting the infrastructure is not so adequate, only in the urban schools that adequate infrastructure facilities.